Medicine use among adolescents: the 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study Utilização de medicamentos por adolescentes: a visita de 11 anos da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993 - Andréa D. Bertoldi; Noemia U. L. Tavares; Pedro C. Hallal; Cora Luiza Araújo; Ana M. B. Menezes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this study was to investigate medicine use and associated factors among adolescents. This was a prospective cohort study including 4,452 adolescents born in Pelotas, Rio Grande do Sul State, Brazil, in 1993. Information on medicine use in the 15 days prior to the interviews was collected from the mothers. Overall prevalence of medicine use was 30.9%, and 64.7% of the medicines had been prescribed by a physician. The most frequently used pharmacological groups were medicines for the nervous (35.9%) and respiratory systems (25.7%). Medicine use was directly associated with socioeconomic status, maternal schooling, complications during pregnancy or delivery, and neonatal problems resulting in the need for intensive care. Underweight and obese adolescents were more likely to use medicines as compared to those with normal body mass index. A direct association was observed between maternal use of hypnotic drugs and sedatives and adolescent medicine use. It is essential to implement educational policies aimed at promoting rational use of medicines by adolescents. O objetivo deste estudo foi investigar o uso de medicamentos e fatores associados em adolescentes. Trata-se de estudo de coorte prospectivo, incluindo 4.452 adolescentes nascidos em Pelotas, Rio Grande do Sul, Brasil, em 1993. As informações sobre o uso de medicamentos pelo adolescente nos 15 dias anteriores à entrevista foram fornecidas pelas mães. A prevalência global de uso de medicamentos foi de 30,9%, sendo que destes, 64,7% foram indicados por médicos. Os grupos farmacológicos mais utilizados foram os medicamentos que atuam nos sistemas nervoso (35,9%) e respiratório (25,7%). O uso de medicamentos esteve diretamente associado ao nível econômico, escolaridade da mãe, intercorrência na gravidez ou parto que gerou doença até a adolescência, problema de saúde no momento do nascimento que levou o recém-nascido à UTI, magreza e obesidade. Foi observada uma relação direta entre uso de medicamentos hipnóticos e sedativos pela mãe e uso de medicamentos pelo adolescente. É fundamental que medidas educativas sejam voltadas à promoção do uso racional de medicamentos nesta faixa etária.